ALKIRE-FOSTER METHOD AND RECOMMENDATIONS FOR CALCULATING THE MULTIDIMENSIONAL POVERTY INDEX (Marketing Journal, 2025)
The article analyzes the essence and effectiveness of the Alkire -Foster method for calculating the multidimensional poverty index. The Alkire -Foster method extends the income -only approach by integrating a number of social and economic factors in determining multidimensional poverty and provides a comprehensive assessment of peopleʼs living conditions. This method helps to determine the depth and extent of poverty, taking into account various poverty dimensions — indicators based on education, health, housing, living conditions and other social factors. The article outlines the calculation steps, basic principles and advantages of the Alkire -Foster method in measuring poverty. It also describes the application of this method in statistical analysis, its role in reducing errors and uncertainties, and methods for comparing it with widely used statistical classifications around the world.
Keywords: Alkire -Foster method; UNDP; multidimensional poverty index; Autofocus method; poverty line